O direito à intimidade dos filhos em face do poder familiar - Rodrigues, Renato Sansone (2007)
The modification operated for the advent of the Federal Constitution of 1988, meant deep difference in the philosophy of life of the people and in the customs of the Brazilian society, whose consequence in the legislation did not delay to be institutionalized. In the second half of 80 s, while the historical, social and politics transformations in Brazil were operated, the Brazilian woman assumed a new social role, conquering a place of prominence in the economy, the politics and the Brazilian family, with its exit of home to the work market. The study of the family law, who regulates the relations between parents and children, necessarily deserves to be analyzed under the prism of the Federal Constitution of 1988, which brings a new dimension of treatment of this disciplines. The Federal Constitution of 1988 regulate that our Democratic State of Right bases on the dignity of the human being. The Civil Code of 2002 dedicated to the juridical personality in its articles 21 and 11th a treatment differentiated and in agreement to the principles and objectives established in the Federal Constitution. In the Civil Code of 2002, the principle in question can be perceived on the Incises III and IV of article 1.556. The mutual assistance and the mutual respect and consideration are marriage duties, or either, given for the couple, in accordance with the patrimonial and personal possibilities of each one. But it s important to remember that the family power must be exerted and pondered with withheld attention to most important of the principles of the family power, in this case, the principle of the superior interest of the child and the adolescent. Some excess or abuse committed in the exercise of the prerogatives established in the family power will be able to configure breaking of the right of privacy of the son, circumstances that can cause its suspension or its dismissal. 9 One quick analysis of the exercise of the family power attributed to the family parents and the guarantee of the rights of the personality of the children, both foreseeing for the Federal Constitution of 1988, with magnifying principles of familiar solidarity by means of the mutual respect and consideration in relation to the integrant ones of the family are the objective of this work